2013
DOI: 10.1002/jcb.24480
|View full text |Cite
|
Sign up to set email alerts
|

The RhoA pathway mediates MMP‐2 and MMP‐9‐independent invasive behavior in a triple‐negative breast cancer cell line

Abstract: Breast cancer is a heterogeneous disease that varies in its biology and response to therapy. A foremost threat to patients is tumor invasion and metastasis, with the greatest risk among patients diagnosed with triple-negative and/or basal-like breast cancers. A greater understanding of the molecular mechanisms underlying cancer cell spreading is needed as 90% of cancer-associated deaths result from metastasis. We previously demonstrated that the Tamoxifen-selected, MCF-7 derivative, TMX2-28, lacks expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…MDA-MB-231SArfp cells treated with plumbagin for 24 h, mRNA expression levels of MMP-2 and MMP-9 in the matrix metalloproteinases family was decreased. Positive expression of MMP-2 and MMP-9 in tumor cells plays a vital role in their migration and invasion in vivo (26). MMP-9 is especially noted for decomposing the collagenous component of the ECM and devastating basic construction of collagen networks, thereby facilitating local invasion and distant migration (27).…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB-231SArfp cells treated with plumbagin for 24 h, mRNA expression levels of MMP-2 and MMP-9 in the matrix metalloproteinases family was decreased. Positive expression of MMP-2 and MMP-9 in tumor cells plays a vital role in their migration and invasion in vivo (26). MMP-9 is especially noted for decomposing the collagenous component of the ECM and devastating basic construction of collagen networks, thereby facilitating local invasion and distant migration (27).…”
Section: Discussionmentioning
confidence: 99%
“…YAP is the major downstream cascade of Hippo signaling, designated the Hippo-YAP pathway, and has been identified as a candidate oncogene [15][16][17][18][19], Zhang et al showed that RhoA knockdown mediated YAP downregulation, promoting apoptosis and inhibiting cell proliferation, cell cycle progression, and migration [20]. As reviewed by Hall [21], RhoA exerts multiple functions in tumor metastasis by orchestrating the action of multiple downstream effectors and promoting extracellular matrix degradation and reconstruction; Fagan-Solis et al showed that blocking RhoA activity inhibited the invasive behavior of breast cancer cells by inhibiting MMP2 and MMP9 directly [22]. We found that RHOA gene silencing decreased the protein expression of RhoA and its downstream targets YAP, P70S6K, MMP2, and Bcl-xL.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…For example, RhoA depletion diminishes motility, invasion [13,14], and proliferation [15] and increases apoptosis [16,17]. It has been reported that RhoA expression is an independent prognostic factor in gastric cancer, especially diffuse-type gastric cancer [18].…”
Section: Discussionmentioning
confidence: 99%